Kualitas Air Minum Isi Ulang (Amiu) di Kecamatan Tamalatea Kabupaten Jeneponto Provinsi Sulawesi Selatan - Sahdan Mustari (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
The provision of clean water is still one of the priorities in improving the degree of public health, because water is an essential material for living things in this world. This study aims to identify the quality of refill drinking water in Tamalatea District, Jeneponto Regency. This research is a quantitative research with descriptive method which was conducted by testing samples obtained from 6 refill drinking water depots (AMIU) to obtain data related to the quality of refill drinking water as seen from the parameters of color, turbidity and dissolved solids. The results showed that of the 6 samples tested, all of them (100%) met the requirements.